Reactions of diborenes with terminal alkynes: mechanisms of ligand-controlled anti-selective hydroalkynylation, cycloaddition and CC triple bond scission. Issue 27 (22nd June 2021) - Englert, Lukas; Schmidt, Uwe; Dömling, Michael; Passargus, Max; Stennett, Tom E.; Hermann, Alexander; Arrowsmith, Merle; Härterich, Marcel; Müssig, Jonas; Phillipps, Alexandra; Prieschl, Dominic; Rempel, Anna; et al.
Abstract : The outcome of reactions between diborenes and terminal alkynes can be tuned by varying the stabilising Lewis base and/or reaction conditions, to yield either the anti -hydroalkynylation product or [2 + 2] cycloaddition-derived boron heterocycles. Abstract : The reactions of terminal acetylenes with doubly Lewis base-stabilised diborenes resulted in different outcomes depending on the nature of the ligands at boron and the conformation of the diborene (cyclic versus acyclic). N-heterocyclic carbene (NHC)-stabilised diborenes tended to undergo anti -selective hydroalkynylation at room temperature, whereas [2 + 2] cycloaddition was observed at higher temperatures, invariably followed by a C–N bond activation at one NHC ligand, leading to the ring-expansion of the initially formed BCBC ring and formation of novel boron-containing heterocycles. For phosphine-stabilised diborenes only [2 + 2] cycloaddition was observed, followed by a rearrangement of the resulting 1, 2-dihydro-1, 2-diborete to the corresponding 1, 3-isomer, which amounts to complete scission of both the BB double and CC triple bonds of the reactants. The elusive 1, 2-isomer was finally trapped by using a cyclic phosphine-stabilised diborene, which prevented rearrangement to the 1, 3-isomer. Extensive density functional theory (DFT) calculations provide a rationale for the selectivity observed.